KARAKTERISTIK DEWAN KOMISARIS, KARAKTERISTIK PERUSAHAAN, DAN KEBERADAAN RISK MANAGEMENT COMMITTEE - Levi Tri Istorini; Sigit Handoyo (Jurnal Keuangan dan Perbankan, 2014)
The research aimed to demonstrate empirically the relationship of commissioners board characteristics and thecompany characteristics against the existence of Risk Management Committee (RMC) and Separated RiskManagement Committee (SRMC). In this research the characteristics of commissioners board consisted ofindependent commissioners and the size of commissioners board and also characteristics of the companyconsisting of auditors reputation, financial reporting risk, company industry type, company size, and leverage.The population taken in this research was all companies in BEI. The method of data analysis was logisticregression analysis with SPSS version 20. The results of this research showed that the variables that wereproved to have positive and significant influence to the existence of the RMC were independent commissioner,leverage, and the size of the company while the size of commissioners board, auditors reputation, financialreporting risk, and types of industry were not proved to give an influence to the existence of RMC. The researchalso proved that the auditors reputation and the size of company gave positive and significant effect to theexistence of SRMC while independent commissioner variables, the size of commissioners board, financialreport risk, and the type of industry did not have an effect to SRMCs existence.